Implementation of SWOT Analysis in Improving Employee Performance at Elan Chocolate Surabaya - Ilham, Rizky Kharizma; Indah, Pawana Nur; Tondang, Ika Sari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Elan Chocolate Company as one of the best MSMEs in Surabaya does not guarantee to have a good human resource system. This study aims to find out the condition of the Company as seen from the SWOT analysis which aims to improve the performance of Elan Chocolate Surabaya employees. The sample collection method was purposive sampling with a total of 6 respondents. Data collection using interviews assisted by questionnaires. The first objective was analyzed with qualitative descriptive, namely classifying Elan Chocolate Surabaya employees. The second objective was analyzed by likert analysis assisted by a questionnaire by identifying the performance of Elan Chocolate Surabaya employees. The third objective is to analyze the condition of the Company using a SWOT analysis to find out the Company's position in order to find out the Company's best strategy in improving employee performance. The results of the study show that, 1) the classification of employees is quite diverse, but the average employee who graduated from junior high school, has an age range of 20-25 years. 2) Employee performance is assessed, especially in the production division, there are 4 types of assessments, quality, quantity, efficiency, and creativity. The assessment was found to be an average of the total value of the entire production division starting from quality (3.49), quantity (3.54), efficiency (3.53), and creativity (3.53). 3) The results of the SWOT analysis of the Company's condition found a SWOT matrix in Quadrant I. This means that the Company's condition is aggressive. The strategy that must be applied to Elan Chocolate Surabaya is the one that supports the policy of the strategy to improve employee performance. Contribution to Sustainable Development Goals (SDGs)SDG 8: Decent Work and Economic GrowthSDG 4: Quality EducationSDG 9:  Industry, Innovation, and Infrastructure SDG 12:  Responsible Consumption and Production.